Potential loss of business services levy receipts in the Marine and Fisheries Office of East Nusa Tenggara Province - Balukh, Agus Ndolu Min; Nursalam, Nursalam; Sayrani, Laurensius P. (Journal of Sustainable Tourism and Entrepreneurship, 2021)
Purpose: The purpose of this research was to identify the potential loss of business service levies received by the Department of Maritime Affairs and Fisheries, East Nusa Tenggara Province. Research Methodology: This study used a qualitative approach and power analysis using spiral data analysis techniques. The informants consisted of 33 people. Data collection was carried out by qualitative observation, qualitative interviews, qualitative document tracing, and qualitative audio-visual material. Results: There was a potential loss from receiving business service levies at the Department of Maritime Affairs and Fisheries, East Nusa Tenggara Province. Limitations: This research focused on identifying the potential loss of business service levy at the Department of Maritime Affairs and Fisheries, East Nusa Tenggara Province. Contribution: This research can be a scientific source and can be the basis for the Department of Maritime Affairs and Fisheries of East Nusa Tenggara Province in overcoming the potential lost problem. Furthermore, this research can be scientific information for public administration students.